Flexural Behavior of High-Strength Steel and Ultra-High-Performance Fiber-Reinforced Concrete Composite Beams - Jun Xia (Buildings, 2024)
The flexural performance of steel and concrete composite beams can be further enhanced by utilizing advanced construction materials such as ultra-high performance fiber-reinforced concrete (UHPFRC) and high-strength steel. In this paper, the concept of critical elastic moment resistance is proposed and the equation for its estimation is derived. It was found that the high yield strength of steel calls for a narrow UHPFRC top layer to reach the critical state, whereas this ideal condition is not realistic for composite beams with normal-strength steel and UHPFRC. Small-scale composite beams composed of both high-strength and low-strength steel materials were tested under four-point bending to verify the critical state and performance of different types of connectors. The headed studs and plate connectors were first tested through small-scale push-out tests and then implemented in the composite beam with different spacing. The connection utilizing headed studs with 150 mm spacing performed the best among the three tested specimens in helping reach the critical elastic moment resistance. Finite element analyses of the composite beam were performed based on the estimated material properties under axial and biaxial stress conditions and the results align with the experiment results.